Inflammation in areas of fibrosis: The DeKAF prospective cohort. Issue 9 (15th April 2020) - Matas, Arthur J.; Helgeson, Erika S.; Gaston, Robert; Cosio, Fernando; Mannon, Roslyn; Kasiske, Bertram L.; Hunsicker, Lawrence; Gourishankar, Sita; Rush, David; Michael Cecka, J; Connett, John; Grande, Joseph P.
Abstract : Inflammation in areas of fibrosis (i‐IFTA) in posttransplant biopsy specimens has been associated with decreased death‐censored graft survival (DC‐GS). Additionally, an i‐IFTA score ≥ 2 is part of the diagnostic criteria for chronic active TCMR (CA TCMR). We examined the impact of i‐IFTA and t‐IFTA (tubulitis in areas of atrophy) in the first biopsy for cause after 90 days posttransplant (n = 598); mean (SD) 1.7 ± 1.4 years posttransplant. I‐IFTA, present in 196 biopsy specimens, was strongly correlated with t‐IFTA, and Banff i. Of the 196, 37 (18.9%) had a previous acute rejection episode; 96 (49%) had concurrent i score = 0. Unlike previous studies, i‐IFTA = 1 (vs 0) was associated with worse 3‐year DC‐GS: (i‐IFTA = 0, 81.7%, [95% CI 77.7 to 85.9%]); i‐IFTA = 1, 68.1%, [95% CI 59.7 to 77.6%]; i‐IFTA = 2, 56.1%, [95% CI 43.2 to 72.8%], i‐IFTA = 3, 48.5%, [95% CI 31.8 to 74.0%]). The association of i‐IFTA with decreased DC‐GS remained significant when adjusted for serum creatinine at the time of the biopsy, Banff i, ci and ct, C4d and DSA. T‐IFTA was similarly associated with decreased DC‐GS. Of these indication biopsies, those with i‐IFTA ≥ 2, without meeting other criteria for CA TCMR had similar postbiopsy DC‐GS as those with CA TCMR. Those with i‐IFTA = 1 and t ≥ 2, ti ≥ 2 had postbiopsy DC‐GS similar to CA TCMR. Biopsies with i‐IFTA = 1 had similar survival as CA TCMR when biopsy specimens also met Banff criteria for TCMR and/or AMR. Studies of i‐IFTA and t‐IFTA in additional cohorts, integrating analyses of Banff scores meeting criteria for other Banff diagnoses, are needed. Abstract : This study of indication biopsies examines i‐IFTA scores and their association with subsequent graft outcomes.